Understanding learners through a Sociolinguistic lens: A Profile of ESL students in Uzbekistan - Tukhlieva Farangiz Navruz qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper presents a sociolinguistic profile of English as a Second Language (ESL) learners at a vocational college in Tashkent, Uzbekistan, with a focus on how language learning is shaped by learners’ identities, multilingual backgrounds, and socio-economic realities. Drawing on theories of sociolinguistics and language ideology, the study explores how students navigate English learning in a context influenced by limited resources, linguistic diversity, and global language expectations. The analysis reveals how classroom practices that validate local English varieties and emphasize communicative competence over native-like proficiency can empower learners. Task-Based Language Teaching (TBLT) and Content-Based Instruction (CBI) are employed to address learners’ goals and sociolinguistic realities. The paper also discusses ethical and practical implications for assessment, emphasizing fairness, intelligibility, and learner identity. It argues for pedagogical approaches that affirm students' voices and prepare them for real world English use, challenging the dominance of standard language ideologies in language teaching.